Improving Nutritional Quality of Turbinaria murayana Seaweed with Fermentation Technology using Local Microorganisms as Poultry Feed - Sepri Reski; Linda Suhartati; Maria Endo Mahata (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The purpose of this study was to increase the nutritional content of brown seaweed type Turbinaria murayana by using fermentation methods using different local microorganisms (MOL) as ingredients for poultry feed. The material used is brown seaweed type Turbinaria murayana taken from Sungai Nipah Beach, Pesisir Selatan Regency, West Sumatra Province and MOL as an inoculum. The study used a completely randomized design (CRD) with six treatments and four replications. The treatment was fermentation using different MOLs, namely No MOL (Control), Bamboo Shoot MOL, Rice MOL, Fruit MOL, Vegetable MOL and Banana Weevil MOL. The results showed that fermentation of brown seaweed type Turbinaria murayana using different MOL had a very significant effect (P≤0.01) on the levels of dry matter, crude fibre, crude protein and crude fat. The best improvement in the nutritional quality of fermented Turbinaria murayana seaweed was found in the fermentation treatment using fruit MOL with the nutritional content of 95.17% dry matter, 5.27% crude fiber, 21.43% crude protein, and 2.41% crude fat.